Composite film with non-angle-dependent structural color as well as preparation method and application of composite film

By using cellulose nanocrystals, sorbitol, tannic acid, and polylysine to prepare angle-independent structural color composite films, the problems of strong angle dependence and single function of CNC films are solved, realizing multifunctional integration, which is suitable for anti-counterfeiting and smart packaging.

CN121673653APending Publication Date: 2026-03-17NORTHEAST FORESTRY UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610074142.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-20
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Existing cellulose nanocrystal (CNC) based structural color films are highly angle-dependent and have limited functionality, making it difficult to simultaneously achieve non-angle-dependent structural color, active antibacterial properties, stimulus response, and excellent mechanical properties.

Method used

Using cellulose nanocrystals, sorbitol, tannic acid, and polylysine as raw materials, an angle-independent structural color composite membrane is prepared by evaporation-induced self-assembly. Combining the green and environmentally friendly characteristics of biomass materials, a multifunctional integrated membrane is achieved.

Benefits of technology

The prepared composite film has angle-independent structural color, antibacterial properties, humidity-induced response, and high flexibility, with a 12-fold increase in elongation at break, making it suitable for anti-counterfeiting materials and smart packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121673653A_ABST
    Figure CN121673653A_ABST
Patent Text Reader

Abstract

The invention discloses a composite film with a non-angle-dependent structural color as well as a preparation method and application thereof, and belongs to the field of functional film materials. The invention aims to solve the problem that an integrated film with non-angle-dependent structural color, active antibacterial property, stimulus response and excellent mechanical property is difficult to realize by a CNC film at the same time. The invention discloses a composite film with a non-angle-dependent structural color. The composite film is prepared from cellulose nanocrystals, sorbitol, tannic acid and polylysine, the method comprises the following steps: 1, mixing cellulose nanocrystal suspension and sorbitol; 2, adding tannic acid; 3, adding a polylysine solution; and 4, evaporation-induced self-assembly film formation. The method is applied to anti-counterfeiting materials and intelligent packaging materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional membrane materials. Background Technology

[0002] Cellulose nanocrystals (CNCs) have become a research hotspot in green photonic crystal materials due to their renewable, biocompatible, and unique optical properties. Through evaporation-induced self-assembly, they can form chiral nematic photonic thin films, producing structural colors. However, existing CNC-based structural color films face significant bottlenecks: firstly, they often exhibit angle-dependent characteristics, making consumer identification difficult; secondly, their functions are limited, offering only anti-counterfeiting capabilities and lacking the antibacterial and preservation properties required for food packaging. Combining the photonic properties of CNCs with multifunctionality often requires multiple modifications or the introduction of non-natural synthetic components, which violates green chemistry principles and makes it difficult to guarantee biosafety.

[0003] Existing methods for endowing CNC thin films with functionality have significant limitations: synthesizing antibacterial agents such as silver nanoparticles and quaternary ammonium salts to obtain antibacterial loading poses risks of biotoxicity and environmental accumulation; introducing stimulus-responsiveness requires complex chemical grafting modifications, which can easily damage the photonic structure; natural polyphenols such as tannic acid (TA) are mostly used as reinforcing agents or crosslinking agents, failing to simultaneously address the issues of angle dependence and single function; plasticizers such as glycerol, while improving brittleness, weaken mechanical strength and optical quality. Therefore, developing a simple, fully bio-based thin film that can simultaneously achieve angle-independent structural color, active antibacterial properties, stimulus responsiveness, and excellent mechanical properties has become a critical technological bottleneck that urgently needs to be overcome in this field. Summary of the Invention

[0004] This invention aims to address the problem that CNC films cannot simultaneously achieve angle-independent structural color, active antibacterial properties, stimulus response, and excellent mechanical properties in an integrated film, and thus provides a composite film with angle-independent structural color, its preparation method, and its application.

[0005] A non-angle-dependent structural color composite film is prepared from cellulose nanocrystals, sorbitol, tannic acid and polylysine.

[0006] A method for preparing an angle-independent structural color composite film, comprising the following steps:

[0007] 1. The cellulose nanocrystal suspension and sorbitol are mixed to obtain the first mixture;

[0008] 2. Add tannic acid to the first mixture and mix well to obtain the second mixture;

[0009] 3. Add polylysine solution to the second mixture and mix well to obtain the third mixture;

[0010] Fourth, the third mixture is used to form a film by evaporation-induced self-assembly, resulting in a composite film with non-angle-dependent structural color.

[0011] An application of a non-angle-dependent structural color composite film, used in anti-counterfeiting materials and smart packaging materials.

[0012] The beneficial effects of this invention are:

[0013] 1) The raw materials used in this invention are all derived from biomass materials, which are green, environmentally friendly, and biodegradable; the preparation process of the structural color composite film of this invention is carried out in an aquatic environment, and the reaction process does not require high temperature, which has the characteristics of mild reaction conditions and simple operation.

[0014] 2) The structural color composite film of the present invention has angle-independent structural color, antibacterial properties, fruit preservation function, humidity stimulation response, and high flexibility. It has good repeatability and has commercial production potential.

[0015] 3) The structural color composite film of the present invention has an angle-independent structural color. The introduction of cationic polypeptide polylysine makes the interior of the film exhibit a long-range disorder / short-range ordered structure; the angle-independent property can be used to make anti-counterfeiting marks.

[0016] 4) The structural color composite film of the present invention has excellent flexibility and the elongation at break is increased by 12 times, making it easy to industrialize and apply in practice. Attached Figure Description

[0017] Figure 1 The ultraviolet transmission spectrum of the CNC film prepared in Comparative Example 1 is shown.

[0018] Figure 2 The ultraviolet transmission spectrum of the CNC / S / T film prepared in Comparative Example 3;

[0019] Figure 3 The ultraviolet transmission spectrum of the CST-PL4 film prepared in Example 1;

[0020] Figure 4 The ultraviolet transmission spectrum of the CST-PL5 film prepared in Example 2;

[0021] Figure 5 Cross-sectional electron microscope image and 2D-FFT image of the CNC film prepared for Comparative Example 1;

[0022] Figure 6 Cross-sectional electron microscope image and 2D-FFT image of the CST-PL4 film prepared in Example 1;

[0023] Figure 7 A polarizing microscope image of the CST-PL4 film prepared in Example 1;

[0024] Figure 8 Circular dichroism spectra of the CST-PL4 film prepared in Example 1 and the CST-PL5 film prepared in Example 2;

[0025] Figure 9 The anti-counterfeiting effects of the CST-PL4 film prepared in Example 1, the CST-PL6 film prepared in Example 3, the CST-PL2 film prepared in Comparative Example 5, and the CST-PL3 film prepared in Comparative Example 6 are shown in the images.

[0026] Figure 10 Stress-strain diagrams of the CST-PL4 membrane prepared in Example 1, the CNC membrane prepared in Comparative Example 1, the CNC / S membrane prepared in Comparative Example 2, and the CNC / S / T membrane prepared in Comparative Example 3.

[0027] Figure 11 The antibacterial zones of the CST-PL4 membrane prepared in Example 1, the CNC membrane prepared in Comparative Example 1, the CNC / S / T membrane prepared in Comparative Example 3, and the CNC / S / PL membrane prepared in Comparative Example 4 are shown.

[0028] Figure 12 The weight loss rate of strawberries preserved using the CST-PL4 film prepared in Example 1 as a preservation film is shown in the figure.

[0029] Figure 13 Photographs showing the actual effect of the CST-PL4 film prepared in Example 1 as a preservation film for strawberries;

[0030] Figure 14 The humidity response range of the CST-PL4 film prepared in Example 1 based on the peak shift of UV-Vis spectral reflectance;

[0031] Figure 15 The DPPH free radical scavenging rates of the CST-PL4 membrane prepared in Example 1, the CNC membrane prepared in Comparative Example 1, the CNC / S / T membrane prepared in Comparative Example 3, and the CNC / S / PL membrane prepared in Comparative Example 4;

[0032] Figure 16 The water vapor transmission rates of the CST-PL4 membrane prepared in Example 1, the CNC membrane prepared in Comparative Example 1, the CNC / S membrane prepared in Comparative Example 2, the CNC / S / T membrane prepared in Comparative Example 3, and the CNC / S / PL membrane prepared in Comparative Example 4 are as follows:

[0033] Figure 17 Hydrophobic angles of the CST-PL4 membrane prepared in Example 1, the CST-PL5 membrane prepared in Example 2, the CST-PL6 membrane prepared in Example 3, the CNC membrane prepared in Comparative Example 1, the CNC / S membrane prepared in Comparative Example 2, the CNC / S / T membrane prepared in Comparative Example 3, the CST-PL2 membrane prepared in Comparative Example 5, and the CST-PL3 membrane prepared in Comparative Example 6;

[0034] Figure 18 Thermogravimetric analysis of the CST-PL4 membrane prepared in Example 1, the CST-PL5 membrane prepared in Example 2, the CST-PL6 membrane prepared in Example 3, the CNC membrane prepared in Comparative Example 1, the CNC / S / T membrane prepared in Comparative Example 3, the CST-PL2 membrane prepared in Comparative Example 5, and the CST-PL3 membrane prepared in Comparative Example 6.

[0035] Figure 19 This is a schematic diagram of the observation angle in the embodiments and comparative examples. Detailed Implementation

[0036] Specific Implementation Method 1: This implementation method provides a non-angle-dependent structural color composite film, which is prepared from cellulose nanocrystals, sorbitol, tannic acid and polylysine.

[0037] The beneficial effects of this specific implementation method are:

[0038] 1) The raw materials used in this invention are all derived from biomass materials, which are green, environmentally friendly, and biodegradable; the preparation process of the structural color composite film of this invention is carried out in an aquatic environment, and the reaction process does not require high temperature, which has the characteristics of mild reaction conditions and simple operation.

[0039] 2) The structural color composite film of the present invention has angle-independent structural color, antibacterial properties, fruit preservation function, humidity stimulation response, and high flexibility. It has good repeatability and has commercial production potential.

[0040] 3) The structural color composite film of the present invention has an angle-independent structural color. The introduction of cationic polypeptide polylysine makes the interior of the film exhibit a long-range disorder / short-range ordered structure; the angle-independent property can be used to make anti-counterfeiting marks.

[0041] 4) The structural color composite film of the present invention has excellent flexibility and the elongation at break is increased by 12 times, making it easy to industrialize and apply in practice.

[0042] Specific Implementation Method Two: This implementation method differs from Specific Implementation Method One in that the thickness of the composite film with non-angle-dependent structural color is 0.04mm~0.06mm. Everything else is the same as in Specific Implementation Method One.

[0043] Specific Implementation Method 3: This implementation method provides a method for preparing an angle-independent structural color composite film, which is carried out according to the following steps:

[0044] 1. The cellulose nanocrystal suspension and sorbitol are mixed to obtain the first mixture;

[0045] 2. Add tannic acid to the first mixture and mix well to obtain the second mixture;

[0046] 3. Add polylysine solution to the second mixture and mix well to obtain the third mixture;

[0047] Fourth, the third mixture is used to form a film by evaporation-induced self-assembly, resulting in a composite film with non-angle-dependent structural color.

[0048] Specific Implementation Method Four: This implementation method differs from Specific Implementation Method Three in that: the cellulose nanocrystal suspension mentioned in step one is a suspension formed by cellulose nanocrystals in water, and the concentration of the cellulose nanocrystal suspension is 3wt%~8wt%; the length of the cellulose nanocrystals is 60nm~300nm. Everything else is the same as in Specific Implementation Method Three.

[0049] Specific Implementation Method Five: This implementation method differs from Specific Implementation Method Three or Four in that the dry weight ratio of cellulose nanocrystals to sorbitol in the first mixture described in step one is 1:(0.05~0.25). Everything else is the same as in Specific Implementation Method Three or Four.

[0050] Specific Implementation Method Six: This implementation method differs from Specific Implementation Methods Three to Five in that the dry weight ratio of cellulose nanocrystals to tannic acid in the second mixture described in step two is 1:(0.05~0.25). Everything else is the same as in Specific Implementation Methods Three to Five.

[0051] Specific Implementation Method Seven: This implementation method differs from Specific Implementation Methods Three to Six in that the polylysine solution mentioned in step three is an aqueous solution of polylysine, and the concentration of the polylysine solution is 0.5wt%~5wt%. Everything else is the same as in Specific Implementation Methods Three to Six.

[0052] Specific Implementation Method Eight: This implementation method differs from Specific Implementation Methods Three to Seven in that the dry weight of polylysine in the third mixture described in step Three accounts for 2% to 5% of the total dry weight of cellulose nanocrystals, sorbitol, tannic acid, and polylysine. Everything else is the same as in Specific Implementation Methods Three to Seven.

[0053] Specific Implementation Method Nine: This implementation method differs from Specific Implementation Methods Three to Eight in that the film formation by evaporation-induced self-assembly in step four is specifically carried out under conditions of solvent evaporation at a temperature of 15℃~25℃ and a drying humidity of 25%~35%. The rest is the same as in Specific Implementation Methods Three to Eight.

[0054] Specific Implementation Method 10: This implementation method describes an application of a non-angle-dependent structural color composite film, characterized in that it is used in anti-counterfeiting materials and smart packaging materials.

[0055] The beneficial effects of the present invention are verified using the following embodiments:

[0056] Example 1:

[0057] A method for preparing an angle-independent structural color composite film, comprising the following steps:

[0058] 1. The cellulose nanocrystal suspension and sorbitol are mixed to obtain the first mixture;

[0059] 2. Add tannic acid to the first mixture and mix well to obtain the second mixture;

[0060] 3. Add polylysine solution to the second mixture and mix well to obtain the third mixture;

[0061] Fourth, the third mixture was used to form a film by evaporation-induced self-assembly, resulting in a composite film with non-angle-dependent structural color, named CST-PL4 film.

[0062] The cellulose nanocrystal suspension mentioned in step one is a suspension of cellulose nanocrystals formed in water, and the concentration of the cellulose nanocrystal suspension is 3wt%; the length of the cellulose nanocrystals is 60nm~300nm.

[0063] In the first mixture mentioned in step one, the dry weight ratio of cellulose nanocrystals to sorbitol is 85:15.

[0064] In step two, the dry weight ratio of cellulose nanocrystals to tannic acid in the second mixture is 85:15.

[0065] The polylysine solution mentioned in step three is an aqueous solution of polylysine, and the concentration of the polylysine solution is 1 wt%.

[0066] In step three, the dry weight of polylysine in the third mixture accounts for 2.42% of the total dry weight of cellulose nanocrystals, sorbitol, tannic acid and polylysine.

[0067] In step four, the film formation by evaporation-induced self-assembly is specifically carried out by solvent evaporation at a temperature of 15℃~25℃ and a drying humidity of 25%~35%.

[0068] The thickness of the non-angle-dependent structural color composite film described in step four is 0.04 mm to 0.06 mm.

[0069] In this embodiment, sorbitol and tannic acid are used in powder form.

[0070] Example 2: This example differs from Example 1 in that the dry weight of polylysine in the third mixture described in step three accounts for 3.01% of the total dry weight of cellulose nanocrystals, sorbitol, tannic acid, and polylysine; the composite film with non-angle-dependent structural color prepared in step four is named CST-PL5. Everything else is the same as in Example 1.

[0071] Example 3: This example differs from Example 1 in that the dry weight of polylysine in the third mixture described in step three accounts for 3.59% of the total dry weight of cellulose nanocrystals, sorbitol, tannic acid, and polylysine; the composite film with non-angle-dependent structural color prepared in step four is named CST-PL6. Everything else is the same as in Example 1.

[0072] Comparative Example 1: This comparative example differs from Example 1 in that the cellulose nanocrystal suspension was used to form a film by evaporation-induced self-assembly, resulting in a cellulose nanocrystal membrane, named the CNC membrane. Everything else is the same as in Example 1.

[0073] Comparative Example 2: This comparative example differs from Example 1 in that the first mixture prepared in step one is used to form a film by evaporation-induced self-assembly, resulting in a composite film named CNC / S film. Everything else is the same as in Example 1.

[0074] Comparative Example 3: This comparative example differs from Example 1 in that the second mixture prepared in step two is used to form a film by evaporation-induced self-assembly, resulting in a composite film named CNC / S / T film. Everything else is the same as in Example 1.

[0075] Comparative Example 4: This comparative example differs from Example 1 in that: the addition of tannic acid in step two is omitted; the dry weight of polylysine in the third mixture in step three accounts for 2.42% of the total dry weight of cellulose nanocrystals, sorbitol, and polylysine; in step four, the third mixture is used to form a film by evaporation-induced self-assembly, resulting in a composite film named CNC / S / PL film. Everything else is the same as in Example 1.

[0076] Comparative Example 5: This comparative example differs from Example 1 in that the dry weight of polylysine in the third mixture described in step three accounts for 1.23% of the total dry weight of cellulose nanocrystals, sorbitol, tannic acid, and polylysine; the composite film with non-angle-dependent structural color prepared in step four is named CST-PL2. Everything else is the same as in Example 1.

[0077] Comparative Example 6: This comparative example differs from Example 1 in that the dry weight of polylysine in the third mixture described in step three accounts for 1.83% of the total dry weight of cellulose nanocrystals, sorbitol, tannic acid, and polylysine; the composite film with non-angle-dependent structural color prepared in step four is named CST-PL3. Everything else is the same as in Example 1.

[0078] The observation angles mentioned in the following tests are all the angles between the human eye's line of sight and the normal to the thin film. Figure 19 As shown, Figure 19 This is a schematic diagram of the observation angle in the embodiments and comparative examples.

[0079] Figure 1 The ultraviolet transmission spectrum of the CNC film prepared in Comparative Example 1 is shown. Figure 2 The ultraviolet transmission spectrum of the CNC / S / T film prepared in Comparative Example 3; Figure 3 The ultraviolet transmission spectrum of the CST-PL4 film prepared in Example 1; Figure 4 The image shows the UV transmission spectrum of the CST-PL5 film prepared in Example 2. As can be seen from the figure, the peak value of pure CNC membrane shifts by 91 nm as the observation angle increases from 0° to 60°; the peak value of CNC / S / T membrane shifts by 97 nm as the observation angle increases from 0° to 60°; while in Examples 1 and 2, the peak value shifts are only 30 nm and 10 nm, respectively, as the observation angle increases from 0° to 60°. This demonstrates that the quaternary membrane exhibits low angle dependence compared to the pure CNC membrane.

[0080] Figure 5 Cross-sectional electron microscope image and 2D-FFT image of the CNC film prepared for Comparative Example 1; Figure 6 Cross-sectional electron microscope (SEM) images and 2D-FFT images of the CST-PL4 film prepared in Example 1 are shown. As can be seen from the images, the chiral nematic structure in the composite film is confirmed to be preserved in the pure CNC SEM image. In contrast, the SEM image of Example 1 shows a long-range disordered but short-range ordered structure. The 2D-FFT image of the pure CNC film shows a bright band along the direction perpendicular to the center, indicating a significant preferred orientation of the nanostructure corresponding to the SEM. In the 2D-FFT image of Example 1, the sharpness of the bright band gradually decreases while its dispersion increases, indicating that the orientational order of the CNC is disturbed.

[0081] Figure 7 The image shows a polarizing microscope image of the CST-PL4 film prepared in Example 1. As can be seen from the image, the CST-PL4 film exhibits a very obvious birefringence phenomenon under a polarizing microscope, and the fingerprint texture area is clear.

[0082] Figure 8 The circular dichroism (CD) spectra of the CST-PL4 film prepared in Example 1 and the CST-PL5 film prepared in Example 2 are shown in the figure. As can be seen from the figure, the composite film also shows a strong positive signal in the CD spectrum, indicating that the composite film has a left-handed structure. Both the CST-PL4 and CST-PL5 films show positive CD peaks similar to those of the pure CNC film, proving that the chiral nematic structure is retained in the composite film.

[0083] Figure 9The images show the anti-counterfeiting effects of the CST-PL4 film prepared in Example 1, the CST-PL6 film prepared in Example 3, the CST-PL2 film prepared in Comparative Example 5, and the CST-PL3 film prepared in Comparative Example 6. As can be seen from the images, the CST-PL4 and CST-PL6 films show almost no color change with the viewing angle, confirming their angle-independent nature. The CST-PL2 film prepared in Comparative Example 5 and the CST-PL3 film prepared in Comparative Example 6 serve as controls, and their colors change with the viewing angle.

[0084] Figure 10 Stress-strain diagrams are shown for the CST-PL4 film prepared in Example 1, the CNC film prepared in Comparative Example 1, the CNC / S film prepared in Comparative Example 2, and the CNC / S / T film prepared in Comparative Example 3. As can be seen from the figures, the elongation at break of the CST-PL4 film is approximately 6.2%, which is nearly 12 times higher than that of the pure CNC film, and superior to Comparative Examples 1, 2, and 3. The strength of the CST-PL4 film is approximately 28.3 MPa, which is superior to that of Comparative Examples 1 and 3. The results indicate that Example 1 can significantly improve the strength and elongation at break of the film.

[0085] Figure 11 The inhibition zones of the CST-PL4 membrane prepared in Example 1, the CNC membrane prepared in Comparative Example 1, the CNC / S / T membrane prepared in Comparative Example 3, and the CNC / S / PL membrane prepared in Comparative Example 4 are shown in the figure. As can be seen from the figure, the inhibition zone diameter of the CST-PL4 membrane for Staphylococcus aureus is approximately 17.81 mm, and the inhibition zone diameter for Escherichia coli is approximately 14.29 mm. These results are superior to the inhibition zone diameters of Comparative Examples 1, 3, and 4.

[0086] Figure 12 The weight loss rate of strawberries preserved using the CST-PL4 film prepared in Example 1 as a preservation film is shown in the figure. Figure 13 The images show the actual effect of the CST-PL4 film prepared in Example 1 as a preservation film for strawberries. The CST-PL4 film was used to preserve strawberries under the following conditions: indoor storage at a temperature of approximately 15℃~20℃ and a humidity of approximately 25%~35%, to further verify the film's freshness preservation effect. The results showed that strawberries in the control group (without the film) developed mold on the second day, while strawberries sealed with PE film showed signs of spoilage on the first day. In contrast, strawberries wrapped with CST-PL4 did not show signs of spoilage until the sixth day, with a weight loss rate of approximately 12.77±1.10%, significantly lower than the control group. The tests indicate that the composite film prepared in Example 1 effectively inhibits bacterial growth, slows down moisture evaporation, and reduces respiration and oxidation to a certain extent.

[0087] Figure 14The humidity response range of the CST-PL4 film prepared in Example 1 based on the peak shift of its UV-Vis spectral reflectance was measured under relative humidity conditions ranging from 34% to 98%. As shown in the figure, the peak value of the UV-Vis reflectance spectrum of the composite film changes under different humidity levels; with increasing humidity, the peak value exhibits a red shift. At 34% relative humidity, the peak value of the film's UV-Vis reflectance spectrum is 566 nm, while at 98% relative humidity, this value increases to 720 nm, representing a peak shift of 154 nm.

[0088] Figure 15 The DPPH radical scavenging rates of the CST-PL4 membrane prepared in Example 1, the CNC membrane prepared in Comparative Example 1, the CNC / S / T membrane prepared in Comparative Example 3, and the CNC / S / PL membrane prepared in Comparative Example 4 were compared. The results showed that the DPPH radical scavenging rate of CST-PL4 was approximately 91.62%, which was higher than that of Comparative Example 1, Comparative Example 3, and Comparative Example 4.

[0089] Figure 16 The water vapor transmission rates of the CST-PL4 membrane prepared in Example 1, the CNC membrane prepared in Comparative Example 1, the CNC / S membrane prepared in Comparative Example 2, the CNC / S / T membrane prepared in Comparative Example 3, and the CNC / S / PL membrane prepared in Comparative Example 4 were measured. The results showed that the water vapor transmission rate of CST-PL4 was approximately 0.029 g·mm·m. -2 ·h -1 • kPa, which is lower than that of comparative examples 1, 2 and 3, is beneficial for fruit preservation.

[0090] Figure 17 The hydrophobic angles of the CST-PL4 film prepared in Example 1, the CST-PL5 film prepared in Example 2, the CST-PL6 film prepared in Example 3, the CNC film prepared in Comparative Example 1, the CNC / S film prepared in Comparative Example 2, the CNC / S / T film prepared in Comparative Example 3, the CST-PL2 film prepared in Comparative Example 5, and the CST-PL3 film prepared in Comparative Example 6 were compared. The results show that the hydrophobic angle of CST-PL4 is approximately 57.7 ± 1°, which is higher than that of Comparative Example 1 and Comparative Example 2, demonstrating that the addition of polylysine can improve the hydrophobic angle of the film.

[0091] Figure 18 Thermogravimetric analysis (TGA) was performed on the CST-PL4 film prepared in Example 1, the CST-PL5 film prepared in Example 2, the CST-PL6 film prepared in Example 3, the CNC film prepared in Comparative Example 1, the CNC / S / T film prepared in Comparative Example 3, the CST-PL2 film prepared in Comparative Example 5, and the CST-PL3 film prepared in Comparative Example 6. The maximum decomposition temperature of CNC was 191.78℃, and the maximum decomposition temperature of CST-PL4 was 228.11℃. The addition of polylysine can increase the maximum decomposition temperature of the film.

Claims

1. A composite film having a non-angle-dependent structural color, characterized by It is prepared from cellulose nanocrystal, sorbitol, tannic acid and polylysine.

2. The composite film with non-angle-dependent structural color according to claim 1, characterized in that The thickness of the composite film with non-angle-dependent structural color is 0.04mm~0.06mm.

3. The method for preparing an angle-independent structural color composite film as described in claim 1, characterized in that... It is carried out in the following steps: I. The cellulose nanocrystal suspension and sorbitol are mixed to obtain a first mixed solution; II. Tannic acid is added to the first mixed solution and mixed uniformly to obtain a second mixed solution; III. Polylysine solution is added to the second mixed solution and mixed uniformly to obtain a third mixed solution; IV. The third mixed solution is formed into a film by the method of evaporation-induced self-assembly to obtain a composite film with non-angle-dependent structural color.

4. The method for preparing an angle-independent structural color composite film according to claim 3, characterized in that... The cellulose nanocrystal suspension in step I is a suspension formed by cellulose nanocrystal in water, and the concentration of the cellulose nanocrystal suspension is 3wt%~8wt%; the length of the cellulose nanocrystal is 60nm~300nm.

5. The method for preparing an angle-independent structural color composite film according to claim 3, characterized in that... The dry weight ratio of cellulose nanocrystal to sorbitol in the first mixed solution in step I is 1:(0.05~0.25).

6. The method for preparing an angle-independent structural color composite film according to claim 3, characterized in that... The dry weight ratio of cellulose nanocrystal to tannic acid in the second mixed solution in step II is 1:(0.05~0.25).

7. The method for preparing an angle-independent structural color composite film according to claim 3, characterized in that... The polylysine solution in step III is an aqueous solution of polylysine, and the concentration of the polylysine solution is 0.5wt%~5wt%.

8. The method for preparing an angle-independent structural color composite film according to claim 3, characterized in that... The dry weight of polylysine in the third mixed solution in step III accounts for 2%~5% of the total dry weight of cellulose nanocrystal, sorbitol, tannic acid and polylysine.

9. The method for preparing an angle-independent structural color composite film according to claim 3, characterized in that... The method of evaporation-induced self-assembly for film formation in step IV is specifically carried out under the conditions of temperature 15℃~25℃ and dry humidity 25%~35% for solvent volatilization film formation.

10. The use of a composite film having a non-angle dependent structural color according to claim 1, characterized in that It is used for anti-counterfeiting materials and intelligent packaging materials.